2011
DOI: 10.1007/s00606-011-0444-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and morphological variability in Cattleya elongata Barb. Rodr. (Orchidaceae), endemic to the campo rupestre vegetation in northeastern Brazil

Abstract: Cattleya elongata is a rupicolous orchid species spread throughout and endemic to outcrop islands in campo rupestre vegetation of the Chapada Diamantina, northeastern Brazil. We scored nine natural populations of C. elongata for morphological and genetic variability, covering the whole distribution area of the species, using allozymes and ISSR markers and morphometric multivariate analyses. Genetic variability in allozimes was relatively high (H e = 0.12-0.25), and unexpectedly higher than the values based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 44 publications
3
17
0
3
Order By: Relevance
“…However, even species of orchids pollinated by Diptera that fly only short distances have lower genetic structure than species of other plant groups in the campos rupestres (e.g. Borba et al ., , ; Jesus et al ., ; Lambert et al ., ; Azevedo et al ., ; Pereira, Borba & Giulietii, ; Cruz et al ., ; Lousada et al ., ; Barbosa et al ., ; Barbosa, Silva‐Pereira & Borba, ; Lousada, Lovato & Borba, ).…”
Section: Discussionmentioning
confidence: 97%
“…However, even species of orchids pollinated by Diptera that fly only short distances have lower genetic structure than species of other plant groups in the campos rupestres (e.g. Borba et al ., , ; Jesus et al ., ; Lambert et al ., ; Azevedo et al ., ; Pereira, Borba & Giulietii, ; Cruz et al ., ; Lousada et al ., ; Barbosa et al ., ; Barbosa, Silva‐Pereira & Borba, ; Lousada, Lovato & Borba, ).…”
Section: Discussionmentioning
confidence: 97%
“…The majority of population genetic studies have been focused on both epiphytic and terrestrial orchids and was mainly based on isozymes (Á vila-Dı´az & Oyama, 2007;Borba, Felix, Solferini, & Semir, 2001;Murren, 2003;Trapnell, Hamrick, & Nason, 2004) and microsatellites (Da Cruz, Selbach-Schnadelbach, Lambert, Ribeiro, & Borba, 2011;Mun˜oz, Warner, & Albertazzi, 2010;Pinheiro et al, 2012;Stone, Crystal, Devlin, Downer, & Cameron, 2012;Swarts, Sinclair, Krauss, & Dixon, 2009;Vargas, Parra-Tabla, Feinsinger, & Leirana-Alcocer, 2006). Despite the molecular marker used, the few studies in orchids indicated that epiphytes enjoy some of the dispersal advantages of trees (e.g., greater potential for gene flow derived from longer-distance dispersal of pollen and seeds; Borba et al, 2001;Flores-Palacios & Garcı´a-Franco, 2003;, which may attenuate the genetic impacts of habitat fragmentation.…”
Section: Introductionmentioning
confidence: 99%
“…In Cattleya intermedia (Machado-Neto and Vieira, 2011) and Cattleya elongata (Cruz et al, 2011) F ST values were low indicating a high gene flux among plants (0.016 and 0.100 respectivelly), but for Fajardo et al (2014) these values are much higher (from 0.177 in Cattleya labiata to 0.322 in Cattleya granulosa) indicating loss of variability in the last case.…”
Section: Resultsmentioning
confidence: 98%
“…Very few is known about the genetics of Cattleya species; Cattleya intermedia (Machado-Neto and Vieira, 2011) using RAPD; Catleya elongata (Cruz et al, 2011) with isozymes and ISSR; Cattleya coccinea (Novello et al, 2013); with ISSR in Cattleya bicolor, Cattleya labiata and Cattleya schofieldiana (Fajardo et al, 2014) with SSR and one in C. labiata using RAPD and ISSR (Pinheiro et al, 2012). And lesser is known about the inheritance of some characters especially because these plants are perennials and the time between one generation and the following is almost 5 years.…”
Section: Introductionmentioning
confidence: 99%